MODELING THE INFLUENCE OF GRAIN MORPHOLOGY ON THE LASER ENGRAVING PROCESSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The study describes the Monte Carlo modelling of the ablation depth during the laser marking process. The effect of grain size on the resulting roughness is studied. The results were validated by experiments with model samples of pure iron with different grain sizes. The influence of the laser power, speed and raster distance were also studied and commented.